Citrus Black Spot: No Longer an Exotic Disease: PP281/PP281, 1/2011 - Dewdney, Megan M.; Yates, Jamie (EDIS, 2011)
Citrus black spot is an emerging fungal disease that affects Florida citrus. Various symptom types occur about a month before harvest. Black spot has the potential to cause major economic damage to the fresh fruit industry and significant yield loss on processing varieties. This trifold brochure was written by Megan Dewdney and Jamie Yates, and published by the UF Department of Plant Pathology, January 2011. *Jamie Yates' name has changed to Jamie Burrow PP281/PP281: Citrus Black Spot: No Longer an Exotic Disease... A Manageable Disease in the Florida Citrus Industry (ufl.edu)